BEAUVERIA PSEUDOBASSIANA REHNER AND HUMBER, 2011 A NEW ENTOMOPATHOGENIC FUNGUS FROM GARA MOUNTAIN, IRAQ - F. R. Hassan; S. K. Abdullah; L. H.Assaf (Journal of Animal and Plant Sciences, 2020)
There is a growing interest in the exploitation of naturally occurring entomopathogenic microorganisms for the control of pests. Beauveria spp is an important entomopathogenic fungi that used as a biocontrol agent of insect pests. The species Beauveria pseudobassiana Rehner and Humber, 2011 was isolated from soil samples collected from the hibernation site of sunn pest Eurygaster integriceps Puton (The most important insect attacks wheat plants in Iraq) at Gara Mountain, Iraq by using selective medium based on oat meal agar amended with CTAB and cyclohexamide. The isolated species was identified depending on both morphological characteristics and molecular data based on ITS-rDNA region. Using blast search, the sequences exhibited high sequence homology (99%) to the fungus B. pseudobassiana that recorded for the first time in Iraq.
Keywords: Beauveria pseudobassiana; Iraq; Kurdistan region; new record